2020
DOI: 10.1002/hed.26185
|View full text |Cite
|
Sign up to set email alerts
|

What the thyroid cancer patient wants to know: ThyCa survey by the American Head and Neck Society Endocrine Surgery Section

Abstract: Objective To survey a large cohort of thyroid cancer survivors from ThyCa on information needs and expectations of their treatment to better understand the pretreatment counseling, information, and support needs of this population. Methods Anonymous survey of thyroid cancer survivors. Results One thousand one hundred twenty‐four patients with thyroid cancer participated in the survey. Three hundred sixty‐two (37.44%) reported not having had a full understanding of their treatment plan and 407 (46.41%) reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The data reported here are part of a larger study, the earlier results of which were reported separately. 31 Here we describe the result of a qualitative content analysis of 1412 respondents, a larger sample size than the initial work, as the survey remained open for 4 additional weeks. Individuals who responded to 3 or fewer fields and/or had no textual responses were excluded (n = 159).…”
Section: Participantsmentioning
confidence: 99%
“…The data reported here are part of a larger study, the earlier results of which were reported separately. 31 Here we describe the result of a qualitative content analysis of 1412 respondents, a larger sample size than the initial work, as the survey remained open for 4 additional weeks. Individuals who responded to 3 or fewer fields and/or had no textual responses were excluded (n = 159).…”
Section: Participantsmentioning
confidence: 99%
“…A recent survey of 1124 thyroid cancer survivors conducted by the American Head and Neck Society Endocrine Section found that for 46% of patients, the experience of therapy was not "on par" with their expectations. Seventy percent of them had received printed preoperative instructions, but when asked how they would have liked to have had those instructions delivered, 62.5% responded that they would have preferred a printed pamphlet and 13.7% responded that they would have preferred an online website for the information [102]. Patients particularly requested more attention to the management of energy levels (61%), psychological well-being (50%), and weight changes (48%).…”
Section: Preoperative Patient Counselingmentioning
confidence: 99%
“…Surgery is the main method of treating TC ( 3 ). Postoperative patients will have different needs in many aspects such as physical, psychological, spiritual and social ( 4 6 ). Unmet needs can increase negative emotions such as anxiety and depression, reduce diagnosis and treatment compliance and disease coping ability, thereby seriously affecting physical and mental health and quality of life ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%